Analysis of Tour Package Stimulus for Vaccine Recipients in the Pandemic Era Based on Travel Agent’s Perspective - Nurdiansyah, Nurdiansyah; Eddyono, Fauziah; Sukwika, Tatan (The Graduate School of Sahid University, 2024)
The COVID-19 pandemic has had a significant impact on reducing the number of tourists, resulting in a decline in the performance of the tourism sector, including travel agents. In an effort to accelerate the recovery of the tourism sector, the Indonesian Government has released a stimulus package program for people who receive the complete COVID-19 vaccine which is distributed through travel agents. This stimulus program is a trial phase in tourist destinations in the Riau Islands, Jakarta and its surroundings, Borobudur and its surroundings, and Bali. This research aims to analyze the impact of the tourism package stimulus on vaccine recipient communities from the travel agent's perspective. The research data is primary data from the results of filling out a questionnaire which was analyzed using the conjoint analysis method and Pearson's R and Kendall's Tau analysis tests on travel agents who took part in this stimulus program. The results of research on travel agents show that their guests are willing to buy tourism stimulus packages because of the 4 star hotel facilities, family restaurant, spa body treatment, mini bus, complete destinations (natural, cultural, and man-made), and there is a souvenir shop that sells food. and souvenirs, thus the stimulus impacted these businesses only.